FKKSA undergraduate research project writing guidelines - Sumaiya, Zainal Abidin; Nurul Aini, Razali; Rohaida, Che Man; Nurul Sa'aadah, Sulaiman; Hamidah, Abdullah; Rozaimi, Abu Samah; Norazwina, Zainol (Penerbit UMP, 2017)
This module was mainly written for FKKSA students taking the Undergraduate Research Project courses, i.e., BKC3922 and BKC4944. It was specifically developed to provide guidance to students in their writing task. This guideline is divided into four elements, which are research proposal, thesis, technical paper, and poster. Each element explains the must-have information and related examples. We hope this guideline could benefit the students and guide them to complete their writing in a proper manner.